The Feasibility Study of Using Space Vector Modulation Inverters in Two-Level of Integrated Photovoltaic System - Mahmoud Zadehbagheri; Amin Payedar (Institute of Advanced Engineering and Science, 2015)
In this paper a system of integrated photovoltaic converter with vector switching control inverter with the modulation method of spatial two-level has been presented. The structure of the system is presented with the proposed and the structure of the invertors’ voltage source has been reviewed. Space vector modulation control method of two-level in a voltage source inverter and then provide proposed system analysis and keying modes are analyzed and the system designing and with the simulation of MATLAB software and standards of the total harmonic distortion for a few modulation methods for comparison, and evaluation has been proposed. The system has been analyzed in terms of economic. A prototype for assessing and comparing with power of 360w in the output with DC link voltage is 400 V and the module voltage is 46.5v has an efficiency of 97.9% in its output that improved than SPWM of 1.6% and to the PWM of 2.7% and Has been simulated with MATLAB software and compared to with a few examples of the control systems of the sinusoidal pulse width modulation and pulse width modulation. Speed and Switching and performance of the system have been analyzed and methods to reduce switching losses and increase of the system efficiency in the practical examples are proposed. DOI: http://dx.doi.org/10.11591/telkomnika.v14i2.7414